An experimental study on grammatical sensitivity and production competence in Chinese and Spanish EFL learners and its implications on EFL teaching methods - He, Qiaoling; Oltra-Massuet, Isabel (Frontiers in Psychology, 2023)
Abstract: Implicit knowledge acquired by L2 learners determines their language competence, although it remains an issue that to what extent advanced EFL learners can acquire implicit language knowledge. This study aims at finding out whether advanced EFL learners from two different L1s could acquire a level of implicit knowledge of English questions by using the modified Elicited Oral Imitation Task. A total number of 91 participants were recruited, including a native speaker group, a Chinese EFL learner group, and a Spanish EFL group. The study evaluated participants’ implicit language knowledge by assessing two indicators: the grammatical sensitivity index and the production index. Results revealed that both EFL groups displayed a significant difference with the native speaker group in their degree of implicit knowledge of English questions in general. A further comparison of the two indicators showed that while both EFL groups displayed a relatively high grammatical sensitivity to morphosyntactic errors in English questions, their corrective production rate of ungrammatical sentences was notably lower. These results indicate that advanced EFL learners had difficulty in acquiring implicit knowledge of English questions at native speaker’ level. These findings also imply a gap between EFL learners’ language knowledge level and corresponding language production competence. Targeting this gap within the Interaction-based production-oriented approach pedagogical implications based on were suggested for enhancing EFL learners’ language production competence in EFL contexts.